Investigating Outdoor Thermal Comfort of Educational Building Complex in Urban Area: A Case Study in Universitas Kebangsaan, Bandung City - Ramadhan, Try; Jurizat, Aldissain; Syafrina, Andina; Rahmat, Amat (Geographica Pannonica, 2021)
Campus building was a place to accommodate various educational activities, which were both carried out indoors and outdoors. The environment, including the building and its exterior, provided thermal comfort that was influenced by the context, such as the mass of the facility, vegetation, and constructing envelope materials. The microclimate also influenced the environment, such as temperature, wind speed, and humidity. This study aimed to investigate the outdoor thermal comfort of campus building in urban area during summer, while also identifying the influential factors. This research referred to a case study, examining the thermal quality of the educational building environment using ENVI-met software, based on the Predicted Mean Vote (PMV) index as an indicator of outdoor thermal comfort, in Universitas Kebangsaan (UK). The results showed that the outdoor environment had low thermal comfort conditions during the day, as it also had different thermal satisfactory situations, due to differences in physical characteristics in each zone. This characteristics included, (1) The SVF determinant as indicators of the shading factor should be supported by the presence of vegetation and the use of pavement material, (2) Although the wind speed factor does not really affect the thermal comfort in the outdoor space, the interconnection between open gaps is likely to make breeze distribution in the area better. This study offered direction for campus planning, in order to maintain the optimal capacity of the natural environment, such as (1) Strategizing to create a better shadowing factor in the outer space, which was supported by controlling the use of pavement materials, (2) Directing the density of buildings by making open spaces more permeable, in order for better wind distribution in the area. From this study, the campus current conditions and future design development potential was also observed.
Keywords: outdoor thermal comfort, educational building, urban area, micro climate, PMV